The fertility of Latin American and Caribbean women in Spain: adaptation, maintenance or interruption? - Grande, Rafael; del Rey, Alberto (Papeles de Población, 2017)
This paper’s aim is to analyse the fertility behaviour of migrant women from Latin America and the Caribbean in Spain, looking for a relationship between fertility in home and host countries. We specifically discuss the integration of Latin American women, exploring whether they choose to uphold their reproductive behaviour, and therefore the existing level of fertility in their home country or whether, conversely, they adapt to the fertility patterns of the host country. Adopting a longitudinal perspective and applying multivariate survival models to data from the 2007 National Survey of Immigration, we show that adaptation, maintenance and interruption patterns coexist in migrant fertility. Our results highlight the importance that family conditions on arrival have in reproductive behaviour.